2011
DOI: 10.4049/jimmunol.1002136
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 and Canonical NF-κB Signaling Pathways Cooperatively Regulate Foxp3 Transcription

Abstract: Notch3 overexpression has been previously shown to positively regulate the generation and function of naturally occurring regulatory T cells and the expression of Foxp3, in cooperation with the pTα/pre-TCR pathway. In this study, we show that Notch3 triggers the trans activation of Foxp3 promoter depending on the T cell developmental stage. Moreover, we discovered a novel CSL/NF-κB overlapping binding site within the Foxp3 promoter, and we demonstrate that the activation of NF-κB, mainly represented by p65-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…The efficacy of the HDACi treatment was documented by histone H3 hyperacetylation in TSAtreated cells (Figure 1c). TSA treatment also induced downregulation of N3 IC protein levels in the human T-ALL cell line Molt-3 (Figure 1d) and in the previously described preT 2017 cell line, in which the triggering of endogenous N3 IC was induced after 24 h of co-culture on a monolayer of the Notch ligand-expressing murine microvascular endothelial cell line SIEC (Barbarulo et al, 2011) (Figure 1e). Consistently with these data, we observed that TSA treatment also reduces Notch3 HDACi promotes Notch3 degradation through acetylation R Palermo et al signaling, as the mRNA levels of endogenous pTalpha (pta), a N3 IC target gene (Talora et al, 2003), are downregulated in both N3-232T-lymphoma cells and in thymocytes, freshly isolated from N3 IC tg mice ( Figure 1f).…”
Section: Tsa Treatment Regulates Notch3 Signalingsupporting
confidence: 57%
See 1 more Smart Citation
“…The efficacy of the HDACi treatment was documented by histone H3 hyperacetylation in TSAtreated cells (Figure 1c). TSA treatment also induced downregulation of N3 IC protein levels in the human T-ALL cell line Molt-3 (Figure 1d) and in the previously described preT 2017 cell line, in which the triggering of endogenous N3 IC was induced after 24 h of co-culture on a monolayer of the Notch ligand-expressing murine microvascular endothelial cell line SIEC (Barbarulo et al, 2011) (Figure 1e). Consistently with these data, we observed that TSA treatment also reduces Notch3 HDACi promotes Notch3 degradation through acetylation R Palermo et al signaling, as the mRNA levels of endogenous pTalpha (pta), a N3 IC target gene (Talora et al, 2003), are downregulated in both N3-232T-lymphoma cells and in thymocytes, freshly isolated from N3 IC tg mice ( Figure 1f).…”
Section: Tsa Treatment Regulates Notch3 Signalingsupporting
confidence: 57%
“…Cells were treated with TSA (Sigma-Aldrich, Poole, UK), MG132 (Sigma-Aldrich), cycloheximide (Sigma-Aldrich), Vorinostat (Sellek-Chemicals, Houston, TX, USA) and Chloroquine (Sigma-Aldrich) for the times indicated. To trigger Notch3 signaling, preT 2017 cells were co-cultured on a monolayer of the Notch ligand-expressing murine microvascular endothelial cell line SIEC, as previously described (Barbarulo et al, 2011). For in vivo treatement, TSA was administered at 10 mg/kg intraperitoneally once (for 12 h treatment) or daily at 1 mg/kg for 3 weeks, unless otherwise specified.…”
Section: Micementioning
confidence: 99%
“…Both these signaling pathways are thought to be activated in MDA-MB-231 cells and MYC and NF-B have previously been shown to cooperatively regulate transcription of a common set of target genes with Notch (Nakshatri et al, 1997;Lee et al, 2000;Cappellen et al, 2007;Margolin et al, 2009;Barbarulo et al, 2011). In RBPJ-deficient cells, NF-B and MYC binding was enriched at the HEY2 promoter and each of these pathways was required for protection against anoikis.…”
Section: Discussionmentioning
confidence: 90%
“…. Further studies by this group reported that Notch 3 promoted the development of T Reg cells and improved their suppressive activity by upregulating FOXP3 expression 88,89 . In a more physiological setting, T Reg cell exposure to Jagged 2-expressing haematopoietic progenitors induced the activation of Notch 3 signalling and promoted the expansion of T Reg cells that could prevent disease onset in an experimental type 1 diabetes model 90 .…”
Section: The Impact Of Notch On Other T H Cell Subsets In Vivomentioning
confidence: 99%